INTERPRETATION OF THE ISOTOPIC COMPOSITION OF VOLCANIC ROCKS WITH REFERENCE TO THE PROBLEM OF OCEANIC MANTLE HETEROGENEITY - Titaeva N.A. (My University, 2001)
The isotopic compositions of volcanic rocks were interpreted with the use of factor analysis techniques for data treatment. This study is based on more than 200 analyses for the isotopic composition of Pb, Nd, and Sr of volcanic rocks from the Atlantic and Pacific oceans and their adjacent continental areas. In order to compare different treatment techniques for isotopic data, we included into the sampling the "end-members" of the well-known "mantle tetrahedron" proposed by A. Zindler and S.R. Hart (DM, HIMU, EM1, and EM2) and the average values for groups (clusters) of oceanic volcanics, which were distinguished by D.V Rundkvist et al. with the use of factor analysis (F, F + DM, F + EM1, F + EM2, and F + HIMU). Our factor-analysis data have demonstrated that the Pb, Sr, and Nd isotopic composition was controlled by two types of independent geochemical processes. One group (predominantly magmatic) affects the isotopic composition of all of the three elements. The other group determines only the isotopic composition of Pb and is related to the formation of the HIMU reservoir. Factor diagrams demonstrate three groups of sources of oceanic island volcanics (hotspots), which coincide with cluster-analysis data. The isotopic heterogeneity of oceanic volcanic rocks is supposedly controlled by the heterogeneity of the oceanic mantle with which relatively homogeneous deep-seated plume material interacts. The main components determining this heterogeneity are the depleted mantle (DM reservoir); relics of the recycled continental lithosphere, which were submerged into the mantle and variably altered by mantle metasomatism (EM2 when alterations are stronger or EM1 if the alterations are relatively weak); and HIMU. A new model is proposed for the genesis of the HIMU reservoir, which is considered to be a fluid-affected scatter aureole around the recycled continental lithosphere (which forms the DUPAL anomaly). Evidence of the genesis of the isotopic and geochemical signatures of HIMU are discussed in detail, and it is hypothesized that one of the main causes of the fractionation of radiogenic Pb isotopes during the origin of HIMU material could be the so-called "diffusion of radioactive recoil atoms."